Effect of sea level rise on the loss of fresh groundwater resources: case studies of Western American coast and Bay of Bengal - Sarukkalige, Priyantha Ranjan; Kazama, S.; Sawamoto, M. (American Society of Civil Engineers, 2005)
Effect of sea level fluctuations on the movement of the freshwater saltwater interface was analyzed bymeans of a sharp interface model. The simulation was carried out over 100 years period for two casestudies based on available data; western coast of America and the Bay of Bengal and adjacent continental shelf. The position of freshwater-saltwater interface was estimated and it reflects the effect of long term average sea level rise on the position of interface. Using the location of the interface, the related loss of freshwater resources was estimated in both areas and results show that volumetric freshwater losses due to sea level rise is 1%- 5% of the aquifer volume in western American coast and 1%-3% in Bay of Bengal. The effects and influences of the loss of fresh groundwater resources were discussed, considering the groundwater use and groundwater recharge and adaptation proposals were introduced for both areas.